Dissolving Lignin in Water through Enzymatic Sulfation with Aryl Sulfotransferase. Issue 10 (20th April 2017) - Prinsen, Pepijn; Narani, Anand; Hartog, Aloysius F.; Wever, Ron; Rothenberg, Gadi
Abstract: We introduce the concept of using site‐specific sulfation of various lignins for increasing their aqueous solubility and thereby their processability. Using p ‐nitrophenylsulfate as a sulfate source and an aryl sulfotransferase enzyme as catalyst, lignins are easily sulfated at ambient conditions. We demonstrate the specific sulfation of phenolic hydroxyl groups on five different lignins: Indulin AT (Kraft softwood), Protobind 1000 (mixed wheat straw/Sarkanda grass soda) and three organosolv lignins. The reaction proceeds smoothly and the increase in solubility is visible to the naked eye. We then examine the reaction kinetics, and show that these are easily monitored qualitatively and quantitatively using UV/Vis spectroscopy. The UV/Vis results are validated with 31 P NMR spectroscopy of the lignin phenol groups after derivatization with phosphorylation reagent II. In general, the results are more significant with organosolv lignins, as Kraft and soda lignins are produced from aqueous lignocellulose extraction processes. Abstract : S is for solubility : Site‐specific sulfation is introduced and used to increase the aqueous solubility of various lignins, improving then their processability. This concept is demonstrated on five lignins using p ‐nitrophenylsulfate as a sulfate source and an aryl sulfotransferase enzyme as catalyst.